(untitled) (ItalianoLinguadue, 2011)
Il presente studio si dedica a una categoria di dizionari ancora assente nella lessicografia italiana: i dizionari per apprendenti L2. Mentre il mercato italiano è dotato di una serie di dizionari pedagogici ideati per alunni e studenti italiani, un’opera concepita secondo il modello dei leaner’s dictionaries inglesi e tedeschi, esclusivamente indirizzati a utenti stranieri (o di italiano L2 in generale) non esiste. L’articolo descrive le caratteristiche fondamentali di un tale dizionario, comprendenti le definizioni, i rapporti semantico-lessicali e morfosemantici tra i lemmi, i contesti sintagmatici tipici (collocazioni e valenze) e la dimensione pragmatica nel trattamento lessicografico dei segnali discorsivi e dei fraseologismi. Ne risulta chiaramente come dovrebbe essere un learner’s dictionary italiano. Fundamental characteristics of an italian learner’s dictionary This study discusses a category of dictionaries which are still absent from Italian lexicography: dictionaries for L2 learners. While the Italian market offers a series of pedagogical dictionaries designed for Italian pupils ad students, a work along the lines of an English or German learner’s dictionary model, exclusively for foreign learners (or Italian L2 learners in general) does not exist. The article describes the basic characteristics for such a dictionary, including definitions, the semantic-lexical and morphosyntatical relationships between the entries, typical syntagmatic contexts (collocations and valences) and the pragmatic dimension in the lexographical treatment of discourse signals and phraseologisms. It is clear how an Italian learner’s dictionary should be designed.